National Business Cultures: Research Methodology, Content and Role in Provision of International Entrepreneurship - Chebotarov, Ie. (Економічний вісник Донбасу, 2019)
The object of analysis is a complex of methodological principles of economic comparative studies: the studies of national business cultures. The evolution of managerial, communicative and marketing approaches in their consideration is being comprehended. The definition of “national business cultures” is substantiated and the essential phenomena, processes and developmental trends that are reflected in the definition are revealed. Об'єктом аналізу є сукупність методологічних положень економічної компаративістики: дослідження національних ділових культур. Усвідомлюється еволюція менеджерського, комунікативного та маркетингового підходів в їх розгляді. Обґрунтовується дефініція “національні ділові культури” і розкриваються сутнісні явища, процеси і тенденції розвитку, які в ній відображаються. Объектом анализа является совокупность методологических положений экономической компаративистики: исследование национальных деловых культур. Осознается эволюция менеджерского, коммуникативного и маркетингового подходов в их рассмотрении. Обосновывается дефиниция "национальные деловые культуры" и раскрываются сущностные явления, процессы и тенденции развития, которые в ней отражаются.